Regulating Root Fungal Community Using Mortierella alpina for Fusarium oxysporum Resistance in Panax ginseng - Wang, Yan; Wang, Liwei; Suo, Meng; Qiu, Zhijie; Wu, Hao; Zhao, Min; Yang, Hongyan (Frontiers in Microbiology, 2022)
Plant-associated microbes play important roles in plant health and disease. Mortierella is often found in the plant rhizosphere, and its possible functions are not well known, especially in medical plants. Mortierella alpina isolated from ginseng soil was used to investigate its effects on plant disease. The promoting properties and interactions with rhizospheric microorganisms were investigated in a medium. Further, a pot experiment was conducted to explore its effects on ginseng root rot disease. Physicochemical properties, high-throughput sequencing, network co-occurrence, distance-based redundancy analysis (db-RDA), and correlation analysis were used to evaluate their effects on the root rot pathogen. The results showed that Mortierella alpina YW25 had a high indoleacetic acid production capacity, and the maximum yield was 141.37 mg/L at 4 days. The growth of M. alpina YW25 was inhibited by some probiotics (Bacillus, Streptomyces, Brevibacterium, Trichoderma, etc.) and potential pathogens (Cladosporium, Aspergillus, etc.), but it did not show sensitivity to the soil-borne pathogen Fusarium oxysporum. Pot experiments showed that M. alpina could significantly alleviate the diseases caused by F. oxysporum, and increased the available nitrogen and phosphorus content in rhizosphere soil. Additionally, it enhanced the activities of soil sucrase and acid phosphatase. High-throughput results showed that the inoculation of M. alpina with F. oxysporum changed the microbial community structure of ginseng, stimulated the plant to recruit more plant growth-promoting bacteria, and constructed a more stable microbial network of ginseng root. In this study, we found and proved the potential of M. alpina as a biocontrol agent against F. oxysporum, providing a new idea for controlling soil-borne diseases of ginseng by regulating rhizosphere microorganisms.